Review of West Nile virus circulation and outbreak risk in Madagascar: Entomological and ornithological perspectives - (:unkn) unknown (My University, 2016)
West Nile fever (WNF) is a zoonotic disease, occurring nearly globally. In Madagascar, West Nile virus (WNV) was first detected in 1978 from wild birds and the virus is currently distributed across the island, but no epidemic or epizootic period has been recorded. One fatal human case of WNV infection was reported in 2011, suggesting a ''tip of the iceberg'' phenomenon of a possible WNF epidemic/epizootic on the island. The main objective of this literature-based survey is to review patterns of WNV circulation in Madagascar from the entomological and ornithological points of view. Among the 235 mosquito species described from Madagascar, 29 species are widely associated with WNV infection; 16 of them are found naturally infected with WNV on the island and categorized into major, candidate, and potential vectors of WNV according to their vector capacity. This study upholds the hypothesis that WNV enzooticity is independent of annual movements of migratory birds passing through Madagascar. Moreover, the lack of regular migratory bird flux between Africa and Madagascar would reduce the probability of transmission and the subsequent reintroduction of the virus into locally occurring mosquito species. Given that Palearctic migratory birds are strongly implicated in the transmission of WNV, we highlight notable differences in the movements and species diversity of these birds in Madagascar as compared to eastern and northern Africa. Risk factors from this two-pronged approach are presented for the emergence of WNF outbreak.
Keywords: African Research